SRC-1 Knockout Exerts No Effect on Amyloid β Deposition in APP/PS1 Mice - Wu, Qiong; Wang, Bin; Li, Qi-Fa; Zhang, Xuan; Ntim, Michael; Wu, Xue-Fei; Li, Na; Zhu, Dan-Dan; Jiang, Rong; Yang, Jin-Yi; Yuan, Yu-Hui; Li, Shao (Frontiers in Aging Neuroscience, 2020)
Steroid receptor coactivator 1 (SRC-1) is the key coactivator to steroids receptors for their transcriptional activities. Previous studies have shown SRC-1 is abundant in hippocampus and has been implicated in cognition. SRC-1 is also related to some major risk factors for Alzheimer’s disease (AD), such as decline of estrogen and aging, however, whether SRC-1 is involved in the pathogenesis of AD remains unclear. In this study, we established SRC-1 knockout in AD mice by cross breeding SRC-1-/- mutant mice with APP/PS1 transgenic mice, and investigated the expression some synaptic protein, the amyloid β (Aβ) deposition and activation of astrocytes & microglia in the hippocampus of APP/PS1×SRC-1-/- mice. The results showed that SRC-1 knockout neither affects the Aβ plaque and activation of glia, nor changes the expression of synaptic proteins in AD model mice. The above results suggest that the complete deletion of SRC-1 in the embryo exerts no effect on the pathogenesis of APP/PS1 mice. Nevertheless, this study could not eliminate the possible role of SRC-1 in the development of AD due to the lack of observation of other events in AD such as tau hyperphosphorylation and the limitation of the animal model employed.